The Educational YouTube Use: Associations with Mathematical Understanding and Learning Autonomy - Cindy Kawilda Hasibuan; Machrani Adi Putri Siregar (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
The use of digital learning resources has become increasingly relevant in mathematics education, particularly through educational YouTube content that offers flexible and visual learning support. However, its relationship with students’ mathematical conceptual understanding and learning autonomy still requires further empirical examination. This study aimed to analyze the relationship between the use of educational YouTube content and junior high school students’ mathematical conceptual understanding and learning autonomy. A quantitative approach with a correlational design was employed. The participants were 30 seventh-grade students of SMP IT Nurul Fadhilah, selected through simple random sampling from a population of 88 students. Data were collected using a Likert-scale questionnaire to measure the use of educational YouTube content and learning autonomy, and a written test to measure mathematical conceptual understanding. The data were analyzed using descriptive statistics, prerequisite tests, and Pearson product-moment correlation with the assistance of IBM SPSS Statistics. The results showed that the use of educational YouTube content had a positive and significant relationship with students’ learning autonomy (R = 0.385; p = 0.039), but it was not significantly related to mathematical conceptual understanding (R = 0.276; p = 0.148). These findings indicate that educational YouTube content is more closely associated with students’ autonomous learning behavior than with their direct conceptual understanding in mathematics.